Time Capsule Rome Opera Ballet's tributeto de Chirico - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2008)
PALABRAS CLAVE: Giorgio de Chirico, George Balanchine, Serge Lifar, Le bal, La Sonnambula, La Jarre, Apollon, Bacchus et Ariane.